2016
DOI: 10.3390/ijms17111911
|View full text |Cite
|
Sign up to set email alerts
|

SEPT12–NDC1 Complexes Are Required for Mammalian Spermiogenesis

Abstract: Male factor infertility accounts for approximately 50 percent of infertile couples. The male factor-related causes of intracytoplasmic sperm injection failure include the absence of sperm, immotile sperm, immature sperm, abnormally structured sperm, and sperm with nuclear damage. Our knockout and knock-in mice models demonstrated that SEPTIN12 (SEPT12) is vital for the formation of sperm morphological characteristics during spermiogenesis. In the clinical aspect, mutated SEPT12 in men results in oligozoospermi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
0
13
0
2
Order By: Relevance
“…NDC1-mediated ALADIN localization of the nuclear pore complexes is critical for selective nuclear protein introduction (29). The research on NDC1 and Nup107 is mostly about the effects of these two genes on sperm formation and infertility (30,31). The central domain of Nup107 interferes with Apaf-1 nuclear translocation during genotoxic stress, leading to Chk-1 activation, and a significant reduction in cell cycle arrest (32).…”
Section: Nup107 Expression In Su Esophagusmentioning
confidence: 99%
“…NDC1-mediated ALADIN localization of the nuclear pore complexes is critical for selective nuclear protein introduction (29). The research on NDC1 and Nup107 is mostly about the effects of these two genes on sperm formation and infertility (30,31). The central domain of Nup107 interferes with Apaf-1 nuclear translocation during genotoxic stress, leading to Chk-1 activation, and a significant reduction in cell cycle arrest (32).…”
Section: Nup107 Expression In Su Esophagusmentioning
confidence: 99%
“…However, further studies are required to determine the effects of Nup210 binding to calcium muscle differentiation (Gomez-Cavazos and Hetzer, 2015). NDC-1 interacts with SEPTIN to form a complex that is co-expressed at the manchette and neck region of sperm during terminal differentiation in mammalian spermiogenesis (Lai et al, 2016).…”
Section: Central Fg-nups and Transmembrane Nupsmentioning
confidence: 99%
“…SEPT12 dysfunction or a reduction in its expression is affiliated with perturbation of sperm head shaping and tail elongation by affecting the organization of α‐ and β‐tubulins (Kuo et al, ). Besides, SEPT12 forms complexes with sperm‐associated antigen 4 (SPAG4) and NDC1 proteins implicated in maintaining the integrity of the nuclear envelope and facilitation of precise sperm head and tail formation respectively (Lai et al, ; Yeh et al, ). Current investigations have been revealed that SEPT12 +/− chimeric mice are sterile due to drastic sperm pathologies, including immotility, defects of the annulus, round head, bent tail, acrosome break, and disrupted mitochondrial architecture (Lin et al, ; Lin, Kuo, Chiang, & Kuo, ).…”
Section: Introductionmentioning
confidence: 99%